FACTORS RELATED TO COMPLIANCE WITH DIET MANAGEMENT AMONG TYPE 2 DM OUTPATIENTS IN ROYAL PRIMA HOSPITAL: Faktor Yang Berhubungan Dengan Kepatuhaan Diet DM Tipe2 Pasien Rawat Jalan di RSU Royal Prima - Ginting, Rapael; Simanullang, Andry; Siallagan, Gabriel Oktavianus (Jurnal Berkala Epidemiologi, 2025)
Background: Diabetes mellitus in Indonesia is increasing annually, with a 6.7% death rate. This is due to patients not following the recommended diet, with Type 2 DM patients having minimal dietary compliance... Purpose: This study aims to find out the relationship between age, gender, education, knowledge, employment status, family role, and the support of health officials to comply with the diet of outpatients type 2 DM in Royal Prima Medan Hospital. Methods: This research method uses cross-sectional methods of conducting interviews, observations, and questionnaire filling. Data were analyzed by using the SPSS application with the α=5% Chi-Square test and the samples used in this study were patients with outpatients type 2 DM at RSU. Royal Prima Medan Hospital with a total of 64 patients in 2024. Results: The result, it was found that there was a significant relationship between age (OR:0.03, CI 95%: 1.67-15.17), gender (OR:0.01, CI 95%:1.28-10.14), knowledge (OR:0.02, CI 95%:0.10-0.89), family role (OR:0.05, CI 95%:0.06-0.64), and health support (OR:0.01, CI 95%:0.05-0.49) for compliance with the outpatients type 2 DM diet management. But there is no significant relationship between education (OR:0.63, CI 95%:0.29-2.11) and job status (OR:0.79, CI 95%:0.42-3.05) for conformity to the type 2 DM diet. Conclusion: This study found that the variable age was the most dominant risk factor for diet management type 2 DM with an OR of 18.935 with p-value (0.04).